The haunting of hill house eaudiobook - Jackson, Shirley (Blackstone Audio, Inc., and Buck 50 Productions, LLC, 2010)
Now a hit Netflix miniseries directed by Mike Flanagan and starring Michiel Huisman, Carla Gugino, and Timothy Hutton Past the rusted gates and untrimmed hedges, Hill House broods and waits. Four seekers have come to the ugly, abandoned old mansion: Dr. Montague, an occult scholar looking for solid evidence of the psychic phenomenon called haunting; Theodora, his lovely and lighthearted assistant; Eleanor, a lonely, homeless girl well acquainted with poltergeists; and Luke, the adventurous future heir of Hill House. At first, their stay seems destined to be merely a spooky encounter with inexplicable noises and self-closing doors, but Hill House is gathering its powers and will soon choose one of them to make its own. This classic horror novel has been hailed as a perfect work of unnerving terror.